Millimeter-wave digitally intensive frequency generation in CMOS - Wu, Wanghua; Staszewski, Robert Bogdan, 1965-; Long, John R. (John Robert), 1958- (Academic Press is an imprint of Elsevier, 2016)
This book describes the digitally intensive time-domain architectures and techniques applied to millimeter-wave frequency synthesis, with the objective of improving performance and reducing the cost of implementation. Coverage includes system architecture, system level modeling, critical building block design, and digital calibration techniques, making it highly suitable for those who want to learn about mm-wave frequency generation for communication and radar applications, integrated circuit implementation, and time-domain circuit and system techniques.